PRIMARY RESULTS OF LONG-TERM DYNAMIC MONITORING OF CHILDREN WITH BRONCHIAL ASTHMA OF UNCONTROLLED SEVERE PERSISTENT COURSE - L. S. Namazova-Baranova; E. A. Vishnyova; E. A. Dobrynina; A. A. Alekseeva; V. I. Smirnov; J. G. Levina; E. V. Antonova (Union of pediatricians of Russia, 2017)
Background. Patients registers help obtain the latest information about the clinical course of a disease, safety and effectiveness of the medical technology. Objective: Our aim was to analyze the efficiency and safety of omalizumab with children suffering from uncontrolled severe persistent bronchial asthma (BA) according to the data of the developed register. Methods.  A register of patients with severe asthma of uncontrolled course receiving omalizumab in addition to basic therapy has been developed. Results. Results of treatment of 101 children aged 6-17 have been analyzed. The duration of therapy with omalizumab lasted from 1 to 85 months, with a median of 16 (10; 44) months. The drug was used in doses of 75 to 600 mg, with a median of 300 (225; 375) mg. The therapy with omalizumab allowed achieving a better control of the disease (AST test prior to start of therapy - 14 (11; 17) points, in 1 year - 20 (13; 25); p < 0,001); reduction of the volume of daily base therapy (prior to start of therapy, average dose of inhaled corticosteroids in terms of fluticasone was 629 ± 304 mg (n = 15), in 4 years - 524 ± 342 mg; p = 0.065); reduction of the number of aggravations and the need to use short-effectiv   2-agonists.  No adverse systemic effects of the introduction of genetically engineered biological drugs have been found. Conclusion. Register of patients with severe persistent asthma can be used as a tool for long-term  monitoring and integrated assessment of the efficiency and safety of therapy.